Mutations in single FT- and TFL1-paralogs of rapeseed (Brassica napus L.) and their impact on flowering time and yield components - Guo, Yuan; Hans, Harloff; Christian, Jung; Molina, Carlos (Frontiers in Plant Science, 2014)
Rapeseed (Brassica napus L.) is grown in different geographical regions of the world. It is adapted to different environments by modification of flowering time and requirement for cold. A broad variation exists from very early-flowering spring-type to late-flowering winter cultivars which only flower after exposure to an extended cold period. B. napus is an allopolyploid species which resulted from the hybridization between B. rapa and B. oleracea. In Arabidopsis thaliana, the PEBP-domain genes FLOWERING LOCUS-T (FT) and TERMINAL FLOWER-1 (TFL1) are important integrators of different flowering pathways. Six FT and four TFL1 paralogs have been identified in B. napus. However, their role in flowering time control is unknown. We identified EMS mutants of the B. napus winter-type inbreed line Express 617. In total, 103 mutant alleles have been determined for BnC6FTb, BnC6FTa, and BnTFL1-2 paralogs. We chose three non-sense and 15 missense mutant lines (M3) which were grown in the greenhouse. Although only two out of 6 FT paralogs were mutated, 6 out of 8 BnC6FTb mutant lines flowered later as the control, whereas all five BnC6FTa mutant lines started flowering as the non-mutated parent. Mutations within the BnTFL1-2 paralog had no large effects on flowering time but on yield components. F1 hybrids between BnTFL1-2 mutants and non-mutated parents had increased seed number per pod and total seeds per plant suggesting that heterozygous mutations in a TFL1 paralog may impact heterosis in rapeseed. We demonstrate that single point-mutations in BnFT and BnTFL1 paralogs have effects on flowering time despite the redundancy of the rapeseed genome. Moreover, our results suggest pleiotropic effects of BnTFL1 paralogs beyond the regulation of flowering time.